PENGARUH PENGGUNAAN METODE JARIMATIKA TERHADAP KEMAMUAN NUMERIK SISWA KELAS 2 PADA MUATAN MATEMATIKA SDN 110/I DESA TENAM - Yulia Nurhaliza; Yantoro Yantoro; Violita Zahyuni (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
The low quality of education can be caused by the use of inappropriate learning methods. This study aims to determine the effect of the jarimatics method on the numerical ability of second-grade students at SDN 110/I Desa Tenam. The jarimatics method is used to achieve learning objectives and improve students' numerical abilities. In this study, the material used is material for calculating length using standard units. This study used a one-group pretest-posttest research design with a total sample of 36 students. Data collection used a test with multiple choice items given during the pretest and posttest. To measure the prerequisites, use the normality test with the chi-square formula, which results that the data is normally distributed. While testing the hypothesis using the t-test which obtained a tcount of 2.6 and a ttable of 2.03245, which means tcount>ttable which indicates Ho is rejected and Ha is accepted.